Vital Problems Of Professional Ecological Training Of Future Geography Teachers - Ilgizarovich Gaisin, Renat (2019)
The article analyzes the problems of professional ecological training of future geography teachers and the approaches to the educational process ensuring the foundation and development of professional ecological competences. The main aspect of the system of ecological education and up-bringing is the system of ecological activities. Introduction of new original technologies and methods into constant teaching practice affects to significant extent the level of contemporary school education. It is evident that modern ecology has transformed from one of branches of biology into s significant range of knowledge including in practice almost all branches of science. Within the frames of school education as well as biology geography is the major subject in forming ecological competence of a student. The main purpose of ecological education is shaping ecological competence of students with further ecological competency. The aim of the article is to demonstrate the analyses of the model of professional ecological competency of would-be teachers of geography.